Research based theatre in dementia knowledge transfer: views from the front line - Argyle, Elaine; Schneider, Justine M. (Emerald, 2015)
Purpose - Formal ties between the theatre and research dissemination have only recently developed and its general efficacy is largely unknown. Here we aim to redress this neglect by examining the effectiveness of a research based theatrical event in promoting dementia knowledge transfer with a group of front line care workers. The event ran over eight days and consisted of an original theatrical production followed by a chaired audience discussion and workshops.